Fashion trends and forecasting : the fashion futurists' toolkit - Hur, Eunsuk; Hemingray, Caroline; Westland, Stephen (Mastering fashion management., 2025)
"Fashion Trends and Forecasting explores how designers, merchandisers, buyers, marketers and strategists use fashion trend forecasting to predict upcoming trends and understand past or current ones. It explains the importance of trend forecasting for businesses, and how technology such as Artificial Intelligence can help to advance it for the future. Addressing both macro and micro trends, including fashion styles, textiles, and colour trends as well as the impact of technology such as AI and the metaverse, the book offers guidance on how fashion students can address fast-changing consumer needs and demands, and identify wider shifts in the cultural, environmental, political and technological worlds. Case studies from globally-recognised organisations feature in every chapter, highlighting and contextualising theory for students. Discussion questions, further reading and exercises help facilitate class discussion and deeper understanding. Designed to equip the reader with Fashion Forecasting tools, methods and principles in an accessible and clear way, this text is recommended and core reading for students studying Fashion Forecasting, Fashion Buying and Fashion Marketing. Supplementary online resources include a short instructor's manual of points to be used for seminar discussions and chapter-by-chapter PowerPoint slides for instructors"--